Purchasing power parity (PPP) between Iran and ASEAN-5 member countries: An application of panel unit root tests - Abbas, Amini-fard; Seyed Komail, Tayebi (2007)
In this paper, we examined the long-run purchasing power parity (PPP) for the five major ASEAN countries, ASEAN-5 (Malaysia, Indonesia, the Philippines, Singapore and Thailand) and the currency relationship, based on the PPP theory, between ASEAN-5 (as the East Asian side) and Iran (as the West Asian side) by using panel data methods to test for unit roots for period 1975-2005. We thus used five panel unit roots tests: Levin, Lin and Chu (2002), Breitung (2000), IM, Pesaran and Shin (2003), Maddala and Wu (1999), Choi (2001) and Hadri (1999). Except for Breitung test, other tests relied on PPP valued by real exchange rates. By the use of real effective exchange rates, most tests did not reject PPP hypothesis among ASEAN-5 members and between ASEAN-5 and Iran. We also found that real exchange rates among ASEAN-5 countries and between ASEAN and Iran are stationary. Overall, the results obtained imply the existence of a long-run and stationary interaction between currencies of both sides in East and West Asia (ASEAN-5 and Iran), leading to the expansion of bilateral trade and economic integration.